Implementation of Decision Support System for New Employee Selection at PT Triotech Solution Indonesia using SAW Method - Subhan Hafiz Nanda Ginting; Nurmala Sridewi (Politeknik Ganesha Medan, 2024)
The new employee selection process is one of the important activities in human resource management at PT Triotech Solution Indonesia. The selection of the right candidate determines the quality and performance of the company in the future. This research aims to develop and implement a Decision Support System (SPK) that can assist in the selection process of new employees using the Simple Additive Weighting (SAW) method. The SAW method was chosen because it is able to integrate various assessment criteria by giving appropriate weights to each criterion, resulting in a final ranking of candidates that best suits the company's needs. The system is built by collecting candidate data, which includes criteria such as education, work experience, technical skills, and soft skills. The weight for each criterion is determined based on the priorities set by the company management. After that, the SAW method is applied to calculate the total score of each candidate, which is then used to determine the priority order of the best candidates.